The stroke east Saxony pilot project for organized post‐stroke care: a case–control study. Issue 5 (28th April 2016) - Bodechtel, Ulf; Barlinn, Kristian; Helbig, Uwe; Arnold, Katrin; Siepmann, Timo; Pallesen, Lars‐Peder; Puetz, Volker; Reichmann, Heinz; Schmitt, Jochen; Kepplinger, Jessica
Abstract: Background: Low adherence to secondary prevention guidelines in stroke survivors may increase the risk for recurrent stroke and adversely impact quality of life. We aimed to determine the feasibility of a self‐developed standardized post‐stroke pathway and its impact on secondary stroke prevention and long‐term outcome in patients with acute stroke. Methods: Consecutive patients with acute stroke were prospectively included in a standardized post‐stroke pathway accomplished through a single certified CM (case manager), which comprised educational discussions and quarterly checkups for vascular risk factors and adherence to antithrombotic/anticoagulant medication in addition to usual care. At 12 months, we compared achieved target goals for secondary prevention, functional outcome, stroke recurrence, and vascular death with age‐ and gender‐matched controls that received only usual care after stroke. Results: We included 45 cases and 45 controls. The following target goals were more frequently achieved in CM‐patients than in controls: blood pressure (100% vs. 46.2%, P < 0.001), cholesterol (100% vs. 74.4%, P < 0.001), and body mass index (67.4% vs. 46.2%, P = 0.052). The CM‐intervention emerged as an independent predictor of favorable functional outcome (mRS ≤ 2) at 12 months after adjusting for stroke severity and systemic thrombolysis (OR: 4.27; 95%CI:1.2–15.21; P = 0.025). Quality of life was rated significantly higher in CM‐patients than in controls ( P = 0.049). As opposed to controls, none of the cases experienced a recurrent stroke (0% vs. 13.3%; P = 0.026) or suffered from vascular death (0% vs. 6.7%; P = 0.242). Conclusions: Our pilot data suggest that organized post‐stroke care enhances achievement of secondary prevention goals. Its possible effect on stroke recurrence, long‐term disability, and quality of life is currently investigated in a prospective cohort study. Abstract : The Stroke East Saxony Pilot Project for Organized Post‐Stroke Care was case–control study to explore the feasibility of a self‐developed standardized post‐stroke pathway and its impact on secondary stroke prevention and long‐term outcome in patients with acute stroke. These pilot data suggest that organized post‐stroke care enhances achievement of secondary prevention goals.